Strategies for Enhancing Spin-Shuttling Fidelities in Si/SiGe Quantum Wells with Random-Alloy Disorder - Merritt P. Losert; Max Oberländer; Julian D. Teske; Mats Volmer; Lars R. Schreiber; Hendrik Bluhm; S.N. Coppersmith; Mark Friesen (PRX Quantum, 2024)
Coherent coupling between distant qubits is needed for many scalable quantum computing schemes. In quantum dot systems, one proposal for long-distance coupling is to coherently transfer electron spins across a chip in a moving dot potential. Here, we use simulations to study challenges for spin shuttling in Si/SiGe heterostructures caused by the valley degree of freedom. We show that for devices with valley splitting dominated by alloy disorder, one can expect to encounter pockets of low valley splitting, given a long-enough shuttling path. At such locations, intervalley tunneling leads to dephasing of the spin wave function, substantially reducing the shuttling fidelity. We show how to mitigate this problem by modifying the heterostructure composition, or by varying the vertical electric field, the shuttling velocity, the shape and size of the dot, or the shuttling path. We further show that combinations of these strategies can reduce the shuttling infidelity by several orders of magnitude, putting shuttling fidelities sufficient for error correction within reach.